Critical Systems and Processes Affecting the Resilience of Subway Systems to Terrorism Risks - Gomba, Pavla; Bradacova, Isabela (Communications - Scientific letters of the University of Zilina, 2015)
Terrorist attack on the urban transport systems with high concentration of people (such as the subway), depending on its mode, can cause different levels of damage including the elimination of sub-components of fire safety equipment or destruction of passive fire protection. To mitigate the effects of an attack, the resilience of vehicles, as well as efficiency of evacuation of the survivors affected mainly by the availability of adequate emergency exits, the number of evacuees and the local conditions of the process are critical. Based on the experience of previous attacks on the metro systems (Tokyo, London and other incidents), this paper identifies critical systems and processes for management of the emergency situation following a potential terrorist attack, ensuring safe and rapid evacuation and rescue to passengers.